Antielastin B-cell and T-cell immunity in patients with chronic obstructive pulmonary disease. Issue 8 (22nd March 2012) - Rinaldi, Manuela; Lehouck, An; Heulens, Nele; Lavend'Homme, Renaud; Carlier, Vincent; Saint-Remy, Jean-Marie; Decramer, Marc; Gayan-Ramirez, Ghislaine; Janssens, Wim
Abstract : Rationale: Antielastin autoimmunity has been hypothesised to drive disease progression in chronic obstructive pulmonary disease (COPD). The proposed mechanism is currently disputed by conflicting data. The authors aimed to explore antibody responses against elastin in a large and extensively characterised COPD population and to assess elastin-specific peripheral T-cell reactivity in a representative subgroup. Methods: Antielastin antibodies were analysed with indirect ELISA on the plasma of 320 patients with COPD (Global Initiative for Chronic Obstructive Lung Disease 1–4) and 143 smoking controls. In a second group of 40 patients with COPD and smoking controls, T-cell responses against extracellular matrix (elastin, collagen I and collagen V) were determined with enzyme-linked immunosorbent spot (EliSpot) (interferon γ (IFNγ) and interleukin-2) on peripheral blood mononuclear cells and compared with the responses of 11 never-smoking controls. Results: Antielastin antibody titres were not elevated in patients with COPD compared with smoking controls and even decreased significantly with increasing severity of COPD (p<0.001). Lower antielastin antibody titres were also found in a subgroup of patients with CT-proven emphysema. Elastin-specific INFγ-mediated T helper 1 responses could not be revealed in smoking subjects with and without COPD. Collagen I-mediated T-cell responses were also absent, which contrasted with a significant increased anticollagen V response in the smoking controls and patients with COPD compared with the never smokers (p=0.008). Collagen V-mediated T-cell responses could not discriminate between patients with COPD and smoking controls. Conclusion: A systemic immune response against elastin could not be identified in patients with COPD. By contrast, collagen V-mediated autoimmunity was increased in the subgroup of smokers and may potentially contribute to the pathogenesis of COPD.